2019
DOI: 10.1093/hmg/ddz263
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of GWAS and eQTL signals at loci with multiple signals identifies additional candidate genes for body fat distribution

Abstract: Abstract Integration of genome-wide association study (GWAS) signals with expression quantitative trait loci (eQTL) studies enables identification of candidate genes. However, evaluating whether nearby signals may share causal variants, termed colocalization, is affected by the presence of allelic heterogeneity, different variants at the same locus impacting the same phenotype. We previously identified eQTL in subcutaneous adipose tissue from 770 participants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…Of note, only two-thirds of our putative causal associations had strong evidence of colocalization, suggesting that a substantial proportion of the initial findings were likely to be driven by genetic confounding through LD between pQTLs and other disease-causal SNPs. To avoid misleading results, we suggest that for regions with multiple molecular trait QTLs, it is important to consider methods such as PWCoCo, which can avoid the assumptions of traditional colocalization approaches of just a single association signal per region 46 . In the current study, application of PWCoCo identified evidence of colocalization for 23 additional protein-phenotype associations hidden to marginal colocalization 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, only two-thirds of our putative causal associations had strong evidence of colocalization, suggesting that a substantial proportion of the initial findings were likely to be driven by genetic confounding through LD between pQTLs and other disease-causal SNPs. To avoid misleading results, we suggest that for regions with multiple molecular trait QTLs, it is important to consider methods such as PWCoCo, which can avoid the assumptions of traditional colocalization approaches of just a single association signal per region 46 . In the current study, application of PWCoCo identified evidence of colocalization for 23 additional protein-phenotype associations hidden to marginal colocalization 46 .…”
Section: Discussionmentioning
confidence: 99%
“…To avoid misleading results, we suggest that for regions with multiple molecular trait QTLs, it is important to consider methods such as PWCoCo, which can avoid the assumptions of traditional colocalization approaches of just a single association signal per region 46 . In the current study, application of PWCoCo identified evidence of colocalization for 23 additional protein-phenotype associations hidden to marginal colocalization 46 . We note that recent recommendations support the use of colocalization as a follow up analysis to reduce false positives 47 .…”
Section: Discussionmentioning
confidence: 99%
“…This analysis incorporated information about significantly associated variants for AD risk obtained from a recent large GWAS 25 and lead eQTL variants each defined as the eSNP showing the strongest association with gene expression. Following recommended guidelines, the variants were deemed to be colocalized by a high posterior probability that a single shared variant is responsible for both signals (PP4 > 0.8) 24, 26 . A lower threshold for statistical significance with a false discovery rate (FDR) < 0.05 for eQTL significant results was applied to maximize detection of colocalized pairs.…”
Section: Materials Subjects and Methodsmentioning
confidence: 99%
“…We performed a colocalization analysis using the method similar to that implemented by Wu et al [43]. For the colocalization of eQTL and pQTL signals, we were unable to determine lead eQTL variants that had the strongest evidence of association with mRNA expression because eQTLs were obtained from multiple studies.…”
Section: Colocalization Analysismentioning
confidence: 99%